2016
DOI: 10.7763/ijcea.2016.v7.535
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidative Capacity of Kefir Produced from Goat Milk

Abstract: Abstract-In this present study, the antioxidant properties of kefir produced from goat milk with kefir grains were investigated. The antioxidant capacity of kefir was evaluated by assessing the DPPH (2,2-Diphenyl-1-picrylhydrazyl), the ABTS-based method [2,2'-azino-bis-(3-ethylbenzthiazoline-6-sulphonic acid)] radical-scavenging activity and ferric reducing antioxidant power (FRAP) at different stages of fermentation and storage period. Generally, the antioxidant capacity of goat milk-kefir samples was mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 33 publications
4
41
0
6
Order By: Relevance
“…This is consistent with findings reported by other authors (Shori ; Yilmaz‐Ersan et al . ) who attributed the proteolytic activity of the microorganisms to the breakage of the protein‐polyphenol complexes and thus the release of polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with findings reported by other authors (Shori ; Yilmaz‐Ersan et al . ) who attributed the proteolytic activity of the microorganisms to the breakage of the protein‐polyphenol complexes and thus the release of polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported by Yilmaz‐Ersan et al . () who demonstrated that the DPPH scavenging ability of goat milk kefir fermented by grains was highest in the 8th h of fermentation and the highest value for ABTS was at the beginning of fermentation. At the end of fermentation, the ABTS and DPPH scavenging activity of B‐GR samples were lower than B‐SC, having a shorter fermentation time (12 h).…”
Section: Discussionmentioning
confidence: 98%
“…Yilmaz‐Ersan et al . () determined that DPPH, FRAP and TPC values of goat milk kefir with grain tended to increase with increased storage time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations